2020
DOI: 10.1111/ijfs.14669
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro antifungal effect of fungal chitosan nanocomposite edible coating against strawberry phytopathogenic fungi

Abstract: This study compared the effectiveness of fungal chitosan nanocomposite, chitosan gel and chitosan nanoparticles against strawberry phytopathogenic fungi (Botrytis cinerea; Rhizopus stolonifer and Aspergillus niger). Nanoparticles were prepared by ionic gelation method and characterised by dynamic light scattering and scanning electron microscopy. The influence of the edible coatings on fungal growth was analysed in vitro and in vivo The fungal chitosan nanoparticles presented an average size = 331.1 nm (AE7.21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Chitosan edible coating on blackberries significantly inhibited the growth of Mucor racemosus [215]. The inhibitory efficiency of chitosan against B. cinerea, A. niger, and R. stolonifer was observed in grapes [216] and strawberries [217]. De Oliveira et al (2014) reported that chitosan inhibits spore germination, radial growth, and germ tube elongation and causes morphological changes in spores and hyphae of B. cinerea, P. expansum, and R. stolonifer in strawberries and grapes [218,219].…”
Section: Edible Coatingsmentioning
confidence: 99%
“…Chitosan edible coating on blackberries significantly inhibited the growth of Mucor racemosus [215]. The inhibitory efficiency of chitosan against B. cinerea, A. niger, and R. stolonifer was observed in grapes [216] and strawberries [217]. De Oliveira et al (2014) reported that chitosan inhibits spore germination, radial growth, and germ tube elongation and causes morphological changes in spores and hyphae of B. cinerea, P. expansum, and R. stolonifer in strawberries and grapes [218,219].…”
Section: Edible Coatingsmentioning
confidence: 99%
“…On the other hand, chitosan nanoparticles have been reported to be effective in controlling the infection caused by phytopathogenic fungi such as Botrytis cinerea , Rhizopus stolonifer , and Aspergillus niger in strawberries under both in vivo and in vitro conditions. The nanoparticles produced had an average size of 331.1 nm (±7.21) with a narrow polydispersity index (0.377) and a zeta potential of +34 mV, which demonstrated the cationic character of the nanoparticles that contributed to reducing fungal infection by damaging cell morphology [ 82 ].…”
Section: Anthracnose Management: New Green Alternativesmentioning
confidence: 99%
“…The coating decreased the decaying rate and prevented the fungal growth. Nanoclay and orange peel essential oils have been used for the development of edible coating of citrus (Melo et al., 2020). The combination of different coating materials can slow down the deteriorative changes.…”
Section: Introductionmentioning
confidence: 99%